Annual Plan 1995-96 Assam (General Areas) Volume-II - Planning Commission (Planning Commission, 1995)
Agriculture contributes a major part' in the State economy and Agriculture development is the prime consideration, to go in for making redical changed in the state through the marginal, small and landless farmers. More than 90% of the area under agriculture is maintained. About 82% of the cultivable land belonging to small and marginal farmers. The average size of operational holding.in the state is 1.37 hectare. The highest size being 2004 hectare.
Planning Commission
Government of Assam